The securitisation of migration: Its limits and consequences - Jaskulowski, Krzysztof (International Political Science Review)
For several years, receiving-country states have increasingly defined immigration as a security issue. This article reviews five recent books that analyse the securitisation of migration from different perspectives. The reviewed books address the securitisation of borders, refugees and their protection, and the consequences of securitisation for migrant minorities. All five books offer a valuable contribution to the literature and expand our knowledge. They fill gaps in existing knowledge, review and systematise the literature, and set new directions for future research. They also convincingly demonstrate the dangers and ambivalence of securitisation politics, including thousands of migrants$1 (Bdeaths and difficulties with migrant integration. They provoke the reader to think about alternatives to securitisation. - Reproduced.s
Keywords: Securitisation